Caractérisation De La Sécheresse Climatique Du Bassin Versant D’oum Er Rbia (Maroc) Par Le Biais De L’indice De Précipitation Standardisé (SPI) - Daki, Yousra; Zahour, Ghalem; Lachgar, Rahal; El Hadi, Hassan (European Scientific Journal, ESJ, 2016)
In recent decades, the drought becomes one of the important phenomena resulting from and climate change variability. Its indirect effects in the time can have an economic, agricultural, hydrological or social impact. The aim objective of this study is to characterize the climate drought at the catchment level of Oum Er Rbia (Morocco) for the period 1985/2013 through the calculation of the Standardized Precipitation Index (SPI) for the four stations studied: El Jadida, Safi, Beni Mellal and Khouribga. The Standardized Precipitation Index (SPI) originally proposed by Mckee et al. (1993) is used as an index of follow-up to the drought and recommended by the World Meteorological Organization. The results obtained after the calculation of this index have enabled us to locate the drought periods of more remarkable in their intensity, their duration and their frequency.